System Analysis of a Hybrid Renewable Energy System - Mohamed Najeh Lakhoua; Naoueli Walid; Chakroun Atef (International Journal of Electrical and Computer Engineering (IJECE), 2014)
Renewable energies are important components of sustainable development. Indeed, coupled with a rational use of energy, they reduce the use of conventional energy systems based on resources of fossil and fissile origin, and so therefore the pressures environmental and socio-economic use. Renewable energy aims to offer an energy service to our society at an acceptable price. But on the other hand, the cost of this service has an impact on the local economy, the environment and society in general. Compared to conventional solutions, enhancement of renewable energy creates more jobs, strengthens the local economy, reduces the environmental impact and reduces the lust on the stocks of energy and therefore it is a source of peace. In this paper, we are interested in the study of a hybrid renewable energy system: wind – photovoltaic – accumulator. The objective of this paper is to propose a novel approach of system analysis based on the OOPP method (Objective Oriented Project Planning) of a hybrid renewable energy system.DOI:http://dx.doi.org/10.11591/ijece.v4i3.5880